Effectiveness of lifestyle interventions for treatment of overweight/obesity among children in China: A systematic review and meta-analysis - Li, Bo; Gao, Shan; Bao, Wei; Li, Ming (Frontiers in Endocrinology, 2022)
Background: Pediatric obesity has become a global public health problem. China has the largest population of obese children in the world. It is important to develop effective interventions to control child obesity. This systematic review summarizes proof from randomized controlled trials to assess the efficacy of lifestyle intervention to reduce BMI and metabolic risk factors for overweight / obese Chinese children. Methods: We searched studies from five databases (PubMed, MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, and CNKI). Research that meets the following requirements was included: randomized controlled trials, participants are overweight /obese Chinese children aged ＜18 years old, and the effectiveness of lifestyle interventions is evaluated. Results: 8 randomized controlled trials were included. A significant difference was found between the intervention group and the control group for the BMI changes (mean difference = −1.49; 95% CI: −2.20 to -0.77; p < 0.001). Subgroup analyses consistently demonstrated that effects of lifestyle interventions on BMI change including multiple-component interventions (mean difference = −2.03 kg/m2; 95% CI: −3.62 to -0.43; p < 0.001) were stronger than those only with physical activities or health education; effects of lifestyle interventions on BMI change were also strengthened if duration of intervention last for more than 1 year (mean difference = −3.03 kg/m2; 95% CI: −4.00 to -2.06; p = 0.01) or with age during 12-18 years old (mean difference = −1.90 kg/m2; 95% CI: −3.37 to -0.43; p < 0.001). Conclusions: Lifestyle interventions are effective in reducing BMI in Chinese children with overweight/obesity, and the effectiveness is more profound when the lifestyle intervention includes multiple components, lasts longer than one year, and/or is conducted among teens. These findings provide an important evidence base for developing and implementing potentially effective lifestyle interventions for the treatment of overweight/obesity among Chinese children.